Pengaruh fraksi massa dan ukuran butir basalt terhadap sifat mekanik komposit hibrid serat rotan - Bely Agusti; Tumpal Ojahan Rajagukguk; Slamet Sumardi; Yusup Hendronursito (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
Composite is a material that continues to be developed because of its advantages as an engineering material. With its diverse geographical environment, Indonesia has resources that can use as a composite material, and Lampung Province is no exception, which has basalt and rattan fiber resources. This research is needed to determine the effect of using basalt powder as a filler and rattan fiber as a polyester resin matrix composite reinforcement. Basalt was reduced to size variations of 100, 200, and 325 mesh with 2%, 7%, and 12% mass fractions. Rattan is made into fiber and washed with 5% NaOH, then dried. Rattan fibers were arranged randomly with a fixed mass fraction of rattan at 10% with a fiber size of 2 mm in diameter and 5 cm in length. SHCP 2668 polyester resin matrix with 2% catalyst. The composite was made using the hand lay-up method by pressing 3 tons for 15 minutes and drying the composite. Mechanical testing includes tensile strength test based on ASTM D638 standard and three-point bending test based on ASTM D790, macro test observations to determine the shape of the fracture after mechanical testing. ANOVA analysis showed the significant effect of mass fraction and size of basalt powder on tensile strength with a P-value <5%. The basalt particle size contributed 84% dominantly, while the mass fraction was 15.6% to the tensile sterngth. The grain size of the basalt contributes 62.13% to the flexural strength with a significant effect of P-value <10%. In flexural strength, rattan fiber has more influence than tensile stress. The small grain size of the basalt provides a denser bonding density between the particles than the larger particles. Resin can fill small cavities formed by small particles to make the composite board thicker and more robust.